2021
DOI: 10.2196/17782
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship Between Portal Usage and Self-Efficacious Health Information–Seeking Behaviors: Secondary Analysis of the Health Information National Trends Survey Data

Abstract: Background Patient portals have drawn much attention, as they are considered an important tool for health providers in facilitating patient engagement. However, little is known about whether the intensive use of patient portals contributes to improved management of patients’ health in terms of their confidence in acquiring health information and exercising self-care. There is a lack of randomized trials with these outcomes measured both pre- and postadoption of patient portals. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies, 9,[17][18][19]21,22,[26][27][28]37,38 we found that portal users were more likely to be younger, female, non-Hispanic White, be privately insured, have higher CCI scores and more likely to live in areas with a higher median income and higher educational attainment. A study of the 2017 and 2018 Health Information National Trends Survey (HINTS) showed higher odds of portal use in respondents with a bachelor's degree and incomes in the middle tertile.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, 9,[17][18][19]21,22,[26][27][28]37,38 we found that portal users were more likely to be younger, female, non-Hispanic White, be privately insured, have higher CCI scores and more likely to live in areas with a higher median income and higher educational attainment. A study of the 2017 and 2018 Health Information National Trends Survey (HINTS) showed higher odds of portal use in respondents with a bachelor's degree and incomes in the middle tertile.…”
Section: Discussionsupporting
confidence: 91%
“…28 Likewise, a different study of the 2017 HINTS showed that participants with higher incomes and educational attainment, and who were employed were more likely to access their online medical records. 38 Similar to our study, Goel et al explored patient use of the portal by demographics and used census data for measuring educational attainment and income. 18 They found disparities across age and gender in patients requesting advice from providers through the patient portal, both when not adjusting and adjusting for education and income.…”
Section: Discussionmentioning
confidence: 75%
“…We hypothesized that it mediated the relationship between frequency of portal use and perceived PCC. Self-efficacy in seeking health information was measured using 1 item used in previous studies [ 43 , 44 ]. In cycle 3, this item was worded as such: Overall, how confident are you that you could get advice or information about health or medical topics if you needed it?…”
Section: Methodsmentioning
confidence: 99%
“…In addition, interacting with these tools is often associated with challenges that involve visual hierarchies of information, increasing the interaction burden [ 11 ]. With limited engagement in emerging digital health care tools to support home care, caregivers do not experience the potential benefits of improving home-based health management and communication [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%